Effects of Film Forming Temperature on Corrosion Resistance of Lanthanum Salt Conversion Film on Magnesium Alloys - XU Man - zu, ZOU Zhong - li (Cailiao Baohu)
In order to find out the best film forming temperature of pure lanthanum salt conversion film on the surface of magnesium alloy, lanthanum salt conversion film was prepared on the surface of magnesium alloy at different film forming temperatures. Scanning electron microscopy (SEM), energy dispersive x - ray spectrometer (EDS) and X - ray diffraction (XRD) were used to observe and analyze the surface morphology and composition of the film, the corrosion resistance of the coating was studied by drop test and electrochemical method. Results showed that lanthanum salt conversion film was formed on the surface of magnesium alloy, and there were cracks with different sizes on the surface of the samples under the different film forming temperatures, among which the surface cracks of lanthanum salt conversion film obtained at 20 ℃ were the least; EDS results showed that the lanthanum salt conversion film on the surface of magnesium alloy was mainly composed of La and O elements, XRD results showed that lanthanum hydroxide was the main component of the conversion film; The results of drop experiment showed that the lanthanum salt conversion film obtained at 20 ℃ had the best corrosion resistance, and the electrochemical test results were consistent with the drop experiment results. Compared with the untreated magnesium alloy samples, the self - corrosion potential shifted 865 mV positively, the self - corrosion current density was decreased by 4 orders of magnitude, and the impedance modulus was increased by about 4 orders of magnitude.